PERAN STRATEGIS BUMDES (BADAN USAHA MILIK DESA) DALAM PEMBERDAYAAN EKONOMI DESA - Imelda Kun Wahyuningtyas (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2021)
In accordance with the mandate of Law No.6 of 2014, the formation of Village-Owned Enterprises (BUMDES) is intended to encourage or accommodate all activities to increase community income, both those that develop according to local customs and culture, as well as economic activities that are submitted to be managed by the community. through Government and Local Government programs or projects. As a village business, the establishment of BUMDES is expected to be able to utilize all the potential of the village community in terms of the economy, natural resources and human resources. The establishment of BUMDES in villages is able to absorb village workers, open up productive economic business opportunities, build business networks, improve the welfare of rural communities, and contribute to Village Original Income (PADes). BUMDES is one of the important economic forces owned by the village in the midst of the entry of various national and international business forces. Even during the Covid-19 pandemic, BUMDES became one of the institutions in the village that played an important role in supporting the sustainability of the village economy. BUMDES is expected to become a